Solving Resource Allocation Model by Using Dynamic Optimization Technique for Al-Raji Group Companies for Soft Drinks and Juices - Hasan, Mohammed; Al-Doori, Mohammed Sadiq (Journal of Economics and Administrative Sciences, 2022)
In this paper, the problem of resource allocation at Al-Raji Company for soft drinks and juices was studied. The company produces several types of tasks to produce juices and soft drinks, which need machines to accomplish these tasks, as it has 6 machines that want to allocate to 4 different tasks to accomplish these tasks. The machines assigned to each task are subject to failure, as these machines are repaired to participate again in the production process. From past records of the company, the probability of failure machines at each task was calculated depending on company data information. Also, the time required for each machine to complete each task was recorded. The aim of this paper is to determine the minimum expected time for the completion of all the machines assigned to perform their tasks in the company by using the dynamic optimization technique over finite and infinite horizons. By comparing the results, it was found that the first and second tasks were better than the third and the fourth tasks because the first task and the second one had completed their tasks in a shorter period than the others, they took 1379.2 hours and 1379.3 respectively during  of horizons (stages), while the third task took 1379.4 hours and the fourth task 1379.5 hours. A careful analysis of the situation revealed that the time it takes for each machine to complete its tasks has been reduced, from appropriate planning and quick and effective maintenance can enhance the capacity of the machines and thus reduce time and effort, which contributes to reducing the company's costs and thus maximizing the production capability to increase the company's profits